New Romantic Cyborgs : Romanticism, Information Technology, and the End of the Machine - Coeckelbergh, Mark (Book collections on Project MUSE., 2017)
An account of the complex relationship between technology and romanticism that links nineteenth-century monsters, automata, and mesmerism with twenty-first-century technology's magic devices and romantic cyborgs.